2003
DOI: 10.1002/0471140864.ps1310s31
|View full text |Cite
|
Sign up to set email alerts
|

Use of Protein Phosphatase Inhibitors

Abstract: Reversible protein phosphorylation is recognized as a major mechanism regulating the physiology of plant and animal cells. Virtually every biochemical process within eukaryotic cells is controlled by the covalent modification of key regulatory proteins. This in turn dictates the cellular response to a variety of physiological and environmental stimuli; errors in signals transduced by phosphoproteins contribute to many human diseases. Thus, defining protein phosphorylation events, and specifically, the phosphop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2010
2010
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 25 publications
0
5
0
1
Order By: Relevance
“…Finally, to examine the role of PP2Ac in a more physiological context, we examined Src activation in human platelets treated with PP2Ac selective inhibitor-OA. OA at concentrations of 10 -100 nM is required to inhibit PP2Ac in intact cells, while 10 M can inhibit cellular PP1c activity (15). Compared with the DMSO-treated platelets, phosphorylation of Src Tyr-529 was distinctly reduced (p ϭ 0.009), whereas the level of Src Tyr-418 phosphorylation was enhanced (p ϭ 0.05) in response to 50 nM OA treatment (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…Finally, to examine the role of PP2Ac in a more physiological context, we examined Src activation in human platelets treated with PP2Ac selective inhibitor-OA. OA at concentrations of 10 -100 nM is required to inhibit PP2Ac in intact cells, while 10 M can inhibit cellular PP1c activity (15). Compared with the DMSO-treated platelets, phosphorylation of Src Tyr-529 was distinctly reduced (p ϭ 0.009), whereas the level of Src Tyr-418 phosphorylation was enhanced (p ϭ 0.05) in response to 50 nM OA treatment (Fig.…”
Section: Resultsmentioning
confidence: 87%
“…The anti-Endos activity of purified PP2A-B55α heterotrimers has the same characteristics as the predominant anti-Endos activity in whole cell extracts. In D , the fostriecin used has lost potency during the ∼6 months of storage after the experiments shown in Figure 2 were performed; fostriecin is well known to be somewhat labile in this time frame ( Weiser et al, 2003 ). It is nonetheless clear that both the anti-Endos and anti-CDKS functions of PP2A-B555α display similar dose responses to this drug.…”
Section: Resultsmentioning
confidence: 99%
“…Pharmacological experiments conducted in HEK293 cells demonstrated that PP1, PP2A, and PP2B were not involved in HTT Ser-421 dephosphorylation downstream of D2R activation. These results, along with a sequence similarity screen of HTT Ser-421 surrounding residues, prompted us to turn our attention toward the members of the PPM/PP2C family, which are insensitive to common phosphatase inhibitors (25). Expression of various members of the PPM/PP2C family and the use of a pharmacological inhibitor (127153) along with shRNA experiments point to PPM1A and/or PPM1B as strong candidates for the D2R-mediated dephosphorylation of HTT Ser-421.…”
Section: Discussionmentioning
confidence: 99%
“…Even at 10 M, okadaic acid (OA) was still ineffective at preventing HTT dephosphorylation following apomorphine stimulation (Fig. 1D); at this concentration, OA inhibits PP1 and PP2A but also PP4, PP5, PP6, and PP2B (calcineurin-B, PP3) (22)(23)(24)(25). To ascertain that PP2B was not implicated (OA has an IC 50 of 4 M for PP2B (22)), we used two PP2B-specific inhibitors: cypermethrin and cyclosporin A.…”
Section: D2r Stimulation Promotes Httn660 Dephosphorylation Inmentioning
confidence: 99%